Distress and Coping Strategy among Indonesian Men with Type-2 Diabetes Mellitus - Fajar Ari Nugroho; Rico Budhiarta Chandra; Nike Laila; Sera Rukia; Inggita Kusumastuty; Anggun Rindang Cempaka; Lola Ayu Istifiani; Atifa Nafia Hasantie Latif (Nurse Media: Journal of Nursing)
Background: Type-2 diabetes mellitus (T2DM) can have a notable impact on the psychological and physical well-being of individuals, which in turn affects the management of the condition. Men and women experiencing stress and adopting distinct coping strategies. However, research focusing specifically on T2DM in men is still limited.